(3aUd GdNWGHs - (3CHh HcQ Hf eMeO Hf YHO Gddg Hf OGhO Hf NWGH GdZGabj,J (B636 (3g` s ((3eMeO Hf GdMGL eMeO Hf eMeO Hf YHOGdQMef GdfYGdj s)
(3ChdgG (B:s
(3CeG HYO, aEf UfGYI GdEfTGA ef CLed eG JMdi Hg GdWGdH s
(3BNQgG (B:s
(3cCf GdaJi de jYO jhekG EPG GcJSi hde jc UYdhckG EPG eG JehdG s
(3QSGFd fKQjI ef EfTGAgs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B232s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B5 - (3U (B89 s
Keywords: (3GdCOHs